PENGARUH RETURN ON ASSET, CURRENT RATIO, DAN DEBT TO EQUITY RATIO TERHADAP INCOME SMOOTHING DENGAN UKURAN RETURN SAHAM SEBAGAI VARIABEL PEMODERASI : (Studi Kasus Pada Sub Sektor Food and Beverages yang terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - Wahyuningsih, Rizka; Huda, Syamsul (FKIP Unswagati, 2024)
This research aims to determine and test the influence of Return On Assets, Current Ratio, and Debt To Equity Ratio on Income Smoothing with Stock Return Measures as a Moderating Variable in Food and Beverages Sub-Sector companies listed on the Indonesia Stock Exchange. This research uses secondary data with a research period of 2019-2023. The research population includes all Food and Beverages Sub-Sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The sample in this research was determined using the purposive sampling method. The data analysis technique in this research is descriptive and verification. The data analysis method used is logistic regression analysis with moderated regression analysis. Data was processed using SPSS version 25 software. The research results show that spatially Return On Assets has no effect on Income Smoothing, Current Ratio has an effect on Income Smoothing, Debt to Equity Ratio has an effect on Income Smoothing. The stock return moderation variable is not able to moderate the Return On Assets to Income Smoothing, The stock return moderation variable is able to moderate the Curent Ratio to Income Smoothing, The stock return moderation variable is not able to moderate the Debt to Equity Ratio to Income Smoothing in Food and Beverages Sub Sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. Keyword: Return on Asset, Current Ratio, Debt to Equity Ratio, Income Smoothing, Stock Return